An econometric model of the United Kingdom - Klein, Lawrence R. (Oxford: B. Blackwell, 1961)
The book covers: An Annual Prototype Model; The Quarterly Model; Two Special Problems in the Light of the Model; The Compilation of the Data; and Problems and Procedures of Computation.
Includes bibliographical references.
rpm 18/09/2017
Loans
Keywords: Great Britain